Gender stereotypes in Nancy Meyers’ “The Intern” (2015): A study of film audience response - Ririn Kurnia Trisnawati; Dian Adiarti; Mia Fitria Agustina (EduLite: Journal of English Education, Literature and Culture, 2021)
Previous film studies focusing on gender stereotypes have been sufficiently conducted, yet what remains understudied is the study of film audience about dynamic gender stereotypes shown in one film. Conducting film audience study with the issue of dynamic gender stereotype allows discussions about audience’s perceptions, awareness and underlying knowledge of gender stereotypes. This study attempts to unravel responses collected from thirteen audience of Nancy Meyer’s “The Intern” (2015) and formulates two research objectives i.e. first, to discuss how the audience of “The Intern” perceive the dynamics of gender stereotype depicted in the film and, second, to examine the underlying insights of their perceptions. The incorporated theories are film audience study, serving also as methodological approach, and the discourse of gender stereotype and its changing perspectives. The finding and discussion show that the audience of “The Intern” perceive the inclusion of gender stereotypes and its dynamic change in the film, and their perceptions are followed by several reasons and insights: the story-line of “The Intern” and the audience’s prior knowledge about gender stereotypes. Awareness and sensibility of gender stereotypes are also revealed after watching “The Intern”. Lastly, discussion about the intersection of the audience’s prior knowledge with the exposure about gender stereotype from various resources is also carried out.